Removal of microplastics in water and wastewater: prospects toward a circular economy - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Chitsan Lin; Minh Cuong Ha; Nguyen Thi Thanh Huyen; Adnan Hussain; X. Hoan Nguyen; Woojin Chung; D. Duc Nguyen (Clean Technologies and Environmental Policy, 2026)

Regional assessment of heavy metal–related ecological risks in the Houjing river sediments in Taiwan: A study using indexes and extreme gradient boosting model - Hong Giang Hoang; Mohammed Hadi; Minh Ky Nguyen; Chitsan Lin; Ngoc Son Hai Nguyen; Ha Manh Bui; Huu-Tuan Tran; Thi Thu Huyen Dong (Regional Studies in Marine Science, 2026)

Microalgal–bacterial granule-based wastewater treatment: Effects of COD/N ratio on particle characteristics and nutrient removal - Mai-Duy-Thong Pham; Phuong-Thao Nguyen; Chitsan Lin; Chettiyappan Visvanathan; Xuan-Thanh Bui (Journal of Environmental Chemical Engineering, 2026)

Emerging challenges of microplastic impacts to ecological health and climate change - Minh-Ky Nguyen; Tony R. Walker; Chitsan Lin; D. Nguyen; Sung Su Kim; Woojin Chung; D. Duc Nguyen (Marine Pollution Bulletin, 2026)

Microplastic pollution associated with probabilistic human health risks: Potential hazards, critical factors, challenges, and limitations - Minh-Ky Nguyen; Chitsan Lin; D. Duc Nguyen (Marine Pollution Bulletin, 2025)

Global Occurrence and Environmental Fate of Microplastics in Stormwater Runoff: Unlock the In-depth Knowledge on Nature-Based Removal Strategies - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Hoang-Lam Nguyen; Chitsan Lin; Balal Yousaf; Minh Cuong Ha; Vu Khac Hoang Bui; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Reviews of Environmental Contamination and Toxicology, 2025)

Effect of salinity on the physico-chemical characteristics of microalgal-bacterial granules treating shrimp farming wastewater - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Nhu-Nguyet Phan; Thien-Tai Nguyen; Ky-Phuong-Ha Huynh; Chitsan Lin; Chettiyappan Visvanathan (Journal of Water Process Engineering, 2025)

Characteristics of inland ship and the effect of combined diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) aftertreatment system on their pollutant emissions - Thi-Hieu Le; Zhi-Ping Hsu; Cindy Soo Yun Tan; Cheng-Di Dong; Chitsan Lin; Tsun-Lirng Yang; Xuan-Thanh Bui; Lin-Chi Wang (Environmental Pollution, 2025)

Microplastic characteristics, transport, risks, and remediation in groundwater: a review - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Nelson Rangel-Buitrago; Chitsan Lin; Minh-Thuan Pham; Minh Cuong Ha; Tan Phong Nguyen; Muhammad Shaaban; S. Woong Chang; D. Duc Nguyen (Environmental Chemistry Letters, 2025)

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Plastic wastes for carbon-based materials: Investigations on recent applications towards environmentally sustainable, carbon dioxide capture and green energy - The-Anh Luu; Van-Giang Le; Van-Anh Thai; Minh-Ky Nguyen; Chitsan Lin; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Environmental Pollution, 2025)

Microalgae − bacteria based wastewater treatment systems: Granulation, influence factors and pollutants removal - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Thanh-Son Dao; Linh-Thy Le; Thi-Dieu-Hien Vo; Ky-Phuong-Ha Huynh; Thanh-Binh Nguyen; Chitsan Lin; Chettiyappan Visvanathan (Bioresource Technology, 2025)

Retraction notice to “Organic composts as A vehicle for the entry of microplastics into the environment: A comprehensive review” [Sci. Total Environ. 892 (2023) 164758] - Van-Re Le; Minh-Ky Nguyen; Hoang-Lam Nguyen; Chitsan Lin; Md. Refat Jahan Rakib; Van-Anh Thai; Van-Giang Le; Guilherme Malafaia; Abubakr M. Idris (Science of The Total Environment, 2024)

Cigarette butts in Vietnam's marine environments: From pollution to solutions and prospects - Pham Minh Thuan; Minh-Ky Nguyen; Chitsan Lin; Nelson Rangel-Buitrago; Francois Galgani; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Is micro(nano)plastic contamination in wet atmospheric deposition a prominent issue requiring heightened attention? - Minh-Ky Nguyen; Md. Refat Jahan Rakib; Chitsan Lin; Myung Hwangbo; Jongsun Kim (Journal of Hazardous Materials, 2024)

Review on personal protective equipment: Emerging concerns in micro(nano)plastic pollution and strategies for addressing environmental challenges - Van-Giang Le; Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Tri Quang Hung Nguyen; Nguyen K. Hue; Quoc-Minh Truong; Soon W. Chang; X. Hoan Nguyen; D. Duc Nguyen (Environmental Research, 2024)

Correction to: A mini‑review on plasticrusts: occurrence, current trends, potential threats, and recommendations for coastal sustainability - Minh‑Ky Nguyen; Md. Refat Jahan Rakib; Hoang‑Lam Nguyen; Chitsan Lin; Guilherme Malafaia; Abubakr M. Idris (Environmental Monitoring and Assessment, 2024)

A Review on Analytical Approaches for Ambient Ozone Open Data in Taiwan - Duy-Hieu Nguyen; Chih-Hsiang Liao; Xuan-Thanh Bui; Chung-Shin Yuan; Chitsan Lin (Current Pollution Reports, 2024)

Deseasonalized trend of ground-level ozone and its precursors in an industrial city Kaohsiung, Taiwan - Duy-Hieu Nguyen; Chih-Hsiang Liao; Xuan-Thanh Bui; Lin-Chi Wang; Chung-Shin Yuan; Chitsan Lin (Environmental Pollution, 2024)

Sustainable struggling: decoding microplastic released from bioplastics—a critical review - Wazir Aitizaz Ahsan; Chitsan Lin; Adnan Hussain; Mahshab Sheraz (Environmental Monitoring and Assessment, 2024)

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Occurrence and fate of pharmaceutical pollutants in wastewater: Insights on ecotoxicity, health risk, and state–of–the-art removal - Minh-Ky Nguyen; Chitsan Lin; Xuan-Thanh Bui; Md. Refat Jahan Rakib; Hoang-Lam Nguyen; Quoc-Minh Truong; Hong-Giang Hoang; Huu-Tuan Tran; Guilherme Malafaia; Abubakr M. Idris (Chemosphere, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Review on fate, transport, toxicity and health risk of nanoparticles in natural ecosystems: Emerging challenges in the modern age and solutions toward a sustainable environment - Thien-Khanh Tran; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Thanh-Cong Nguyen; Aasif Mohmad Lone; Akhil Pradiprao Khedulkar; Mohamed S. Gaballah; Jagpreet Singh; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2024)

Evaluate the effect of β-cyclodextrin on the sensory and physicochemical properties of bitter gourd extract during thermal processing - Cam Thi Hong Tran; Hui-Min David Wang; Le Thi Hong Anh; Chitsan Lin; Chun-Yung Huang; Chia-Hung Kuo (Food Chemistry, 2024)

Spatiotemporal variation and inter-transport of atmospheric speciated mercury between Kaohsiung Harbor and neighboring urban areas - I-Chieh Tu; Chung-Shin Yuan; Yu-Lun Tseng; Chia-Wei Lee; Chitsan Lin (Environmental Pollution, 2024)

A mini-review on plasticrusts: occurrence, current trends, potential threats, and recommendations for coastal sustainability - Minh-Ky Nguyen; Md. Refat Jahan Rakib; Hoang-Lam Nguyen; Chitsan Lin; Guilherme Malafaia; Abubakr M. Idris (Environmental Monitoring and Assessment, 2024)

Mitigation of ammonia emissions during food waste composting through acetic acid addition: A promising strategy for sustainable waste management - Adnan Hussain; Wen-Yen Huang; Chun-Yu Lin; Wazir Aitizaz Ahsan; Chitsan Lin (Sustainable Chemistry and Pharmacy, 2023)

A comprehensive review of micro- and nano-plastics in the atmosphere: Occurrence, fate, toxicity, and strategies for risk reduction - Van-Giang Le; Minh-Ky Nguyen; Hoang-Lam Nguyen; Chitsan Lin; Mohammed Hadi; Nguyen Tri Quang Hung; Hong-Giang Hoang; Khoi Nghia Nguyen; Huu-Tuan Tran; Deyi Hou; Tao Zhang; Nanthi S. Bolan (Science of The Total Environment, 2023)

Influence of salinity on microalgae-bacteria symbiosis treating shrimp farming wastewater - Thi-Kim-Quyen Vo; Quang-Huy Hoang; Huu Hao Ngo; Cong-Sac Tran; Tung N.N. Ninh; Song-Lam Le; An-Tan Nguyen; Tan Thi Pham; Thanh-Binh Nguyen; Chitsan Lin; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

A review on sterilization methods of environmental decontamination to prevent the coronavirus SARS-CoV-2 (COVID-19 virus): A new challenge towards eco-friendly solutions - Nguyen Trung Hiep; Minh-Ky Nguyen; Huynh Tan Nhut; Nguyen Tri Quang Hung; Nguyen Cong Manh; Chitsan Lin; S. Woong Chang; Myoung Jin Um; D. Duc Nguyen (Science of The Total Environment, 2023)

Occurrence, fate, and potential risk of pharmaceutical pollutants in agriculture: Challenges and environmentally friendly solutions - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Nguyen Tri Quang Hung; D. Duong La; X. Hoan Nguyen; S. Woong Chang; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2023)

Ecotoxicity of micro- and nanoplastics on aquatic algae: Facts, challenges, and future opportunities - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Van-Giang Le; S. Haddout; Myoung-Jin Um; Soon W. Chang; D. Duc Nguyen (Journal of Environmental Management, 2023)

Properties of the mixing layer height retrieved from ceilometer measurements in Slovakia and its relationship to the air pollutant concentrations - Duy-Hieu Nguyen; Dušan Štefánik; Tereza Šedivá; Chitsan Lin (Environmental Science and Pollution Research, 2023)

Enhanced biodegradation of endocrine disruptor bisphenol A by food waste composting without bioaugmentation: Analysis of bacterial communities and their relative abundances - Adnan Hussain; Suei Chang Wu; Thi-Hieu Le; Wen-Yen Huang; Chitsan Lin; Xuan-Thanh Bui; Huu Hao Ngo (Journal of Hazardous Materials, 2023)

Emergence of microplastics in the aquatic ecosystem and their potential effects on health risks: The insights into Vietnam - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Van-Re Le; Priya KL; Jagpreet Singh; Soon W. Chang; Myoung-Jin Um; D. Duc Nguyen (Journal of Environmental Management, 2023)

RETRACTED: Organic composts as A vehicle for the entry of microplastics into the environment: A comprehensive review - Van-Re Le; Minh-Ky Nguyen; Hoang-Lam Nguyen; Chitsan Lin; Md. Refat Jahan Rakib; Van-Anh Thai; Van-Giang Le; Guilherme Malafaia; Abubakr M. Idris (Science of The Total Environment, 2023)

Succession of biochar addition for soil amendment and contaminants remediation during co-composting: A state of art review - Huu-Tuan Tran; Nanthi S. Bolan; Chitsan Lin; Quach An Binh; Minh-Ky Nguyen; The Anh Luu; Van-Giang Le; Cham Q. Pham; Hong-Giang Hoang; Dai-Viet N. Vo (Journal of Environmental Management, 2023)

Characterization of reciprocation membrane bioreactor on treatment performance, energy consumption and membrane fouling - Phuong-Thao Nguyen; Duyen Phuc Hanh Tran; Linh-Thy Le; Chitsan Lin; Le Thi Kim Oanh; Van-Tung Tra; Xuan-Thanh Bui (Bioresource Technology, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Application of vetiver grass (Vetiveria Zizanioides L.) for organic matter removal from contaminated surface water - Minh Ky Nguyen; Nguyen Tri Quang Hung; Cong Manh Nguyen; Chitsan Lin; Tuan Anh Nguyen; Hoang-Lam Nguyen (Bioresource Technology Reports, 2023)

Characterization of VOCs during diesel oil composting process - Tachen Lin; Shulung Kuo; Adnan Hussain; Zhigui Chen; Manlin Huang; Chitsan Lin (Bioresource Technology Reports, 2023)

Succession of microbial communities with VOC changes during composting process - Tachen Lin; Yunlong Zhao; Yuan Jiang; Jinlan Ou; Adnan Hussain; Lixian Chen; Chitsan Lin (Bioresource Technology Reports, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

Chemical fingerprints and source resolution of atmospheric fine particles in an industrial harbor based on one-year intermittent field sampling data - Yu-Lun Tseng; Chung-Shin Yuan; Kwok-Wai Wong; Chitsan Lin (Science of The Total Environment, 2023)

Investigation of biochar amendments on odor reduction and their characteristics during food waste co-composting - Minh Ky Nguyen; Chitsan Lin; Hong Giang Hoang; Xuan Thanh Bui; Huu Hao Ngo; Van Giang Le; Huu-Tuan Tran (Science of The Total Environment, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

Investigation of ecological risk of microplastics in peatland areas: A case study in Vietnam - Minh Ky Nguyen; Chitsan Lin; Nguyen Tri Quang Hung; Hong-Giang Hoang; Dai-Viet N. Vo; Huu-Tuan Tran (Environmental Research, 2023)

Ecological risk assessment and corrective actions for dioxin-polluted sediment in a chemical plant's brine water storage pond - Chi-Wei Huang; Wen-Yen Huang; Chitsan Lin; Yi-Lin Li; Tsung-Po Huang; Xuan-Thanh Bui; Huu Hao Ngo (Science of The Total Environment, 2023)

Seasonal influence on pollution index and risk of multiple compositions of microplastics in an urban river - Chi-Wei Huang; Yi-Lin Li; Chitsan Lin; Xuan-Thanh Bui; Thi-Dieu-Hien Vo; Huu Hao Ngo (Science of The Total Environment, 2023)

Solvent-Based Soil Washing of Mercury-Contaminated Soil with Eco-friendly Washing Agents - Wazir Aitizaz Ahsan; Hong-Giang Hoang; Qiong-Jia Zhang; Chitsan Lin; Wen-Yen Huang; Minh Ky Nguyen; Adnan Hussain (Water, Air, & Soil Pollution, 2023)

Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test - Huu-Tuan Tran; Chitsan Lin; Su Shiung Lam; Thi Hieu Le; Hong-Giang Hoang; Xuan-Thanh Bui; Eldon R. Rene; Po Han Chen (Environmental Pollution, 2023)

Volatile organic compounds in ambient air of a major Asian port: spatiotemporal variation and source apportionment - Thi-Hieu Le; Chitsan Lin; Duy-Hieu Nguyen; Nicholas Kiprotich Cheruiyot; Chung-Shin Yuan; Chung-Hsuang Hung (Environmental Science and Pollution Research, 2022)

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

A five-year investigation of water quality and heavy metal mass flux of an industrially affected river - Gavin Yeh; Chitsan Lin; Duy-Hieu Nguyen; Hong-Giang Hoang; Jian-Chuan Shern; Pu-Jen Hsiao (Environmental Science and Pollution Research, 2022)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

The Individual and Synergistic Indexes for Assessments of Heavy Metal Contamination in Global Rivers and Risk: a Review - Hong-Giang Hoang; Chitsan Lin; Chow-Feng Chiang; Xuan-Thanh Bui; Wisanukorn Lukkhasorn; Thi-Phuong-Thuy Bui; Huu-Tuan Tran; Thi-Dieu-Hien Vo; Van-Giang Le; Long D. Nghiem (Current Pollution Reports, 2021)

Assessment of heavy metal contamination and adverse biological effects of an industrially affected river - Gavin Yeh; Hong-Giang Hoang; Chitsan Lin; Xuan-Thanh Bui; Huu-Tuan Tran; Chien-Chuan Shern; Chi-Thanh Vu (Environmental Science and Pollution Research, 2020)

Ultrasonic Soil Washing with Fish Oil Extract to Remove Polychlorinated Dibenzo-p-dioxins (PCDDs), Dibenzofurans (PCDFs) from Highly Contaminated Field Soils - Chi Thanh Vu; Chitsan Lin; Weiteng Hung; Wen-Yen Huang; Acharee Kaewlaoyoong; Siwalee Yotapukdee; Jenq-Renn Chen; Yun-Hwei Shen (Water, Air, & Soil Pollution, 2017)

Bioaccumulation and potential sources of heavy metal contamination in fish species in Taiwan: assessment and possible human health implications - Chi Thanh Vu; Chitsan Lin; Gavin Yeh; Maria Ching Villanueva (Environmental Science and Pollution Research, 2017)

The use of ultrasound-assisted anaerobic compost tea washing to remove poly-chlorinated dibenzo-p-dioxins (PCDDs), dibenzo-furans (PCDFs) from highly contaminated field soils - Weiteng Hung; Wen-Yen Huang; Chitsan Lin; Chi Thanh Vu; Siwalee Yotapukdee; Acharee Kaewlaoyoong; Jenq-Renn Chen; Yun-Hwei Shen (Environmental Science and Pollution Research, 2017)

Green and sustainable remediation (GSR) evaluation: framework, standards, and tool. A case study in Taiwan - Wen-Yen Huang; Weiteng Hung; Chi Thanh Vu; Wei-Ting Chen; Jhih-Wei Lai; Chitsan Lin (Environmental Science and Pollution Research, 2016)

Distribution Of Volatile Organic Compounds In Ambient Air Of Kaohsiung, Taiwan - Yu-Jue Hong; Hueiwang Anna Jeng; Yang-Yen Gau; Chitsan Lin; I-Long Lee (Environmental Monitoring and Assessment, 2006)